Vascular Density in Retina and Choriocapillaris as Measured by Optical Coherence Tomography Angiography - Wang, Qian; Chan, Szyyann; Yang, Jing Yan; You, Bing; Wang, Ya Xing; Jonas, Jost B.; Wei, Wen Bin (American journal of ophthalmology, 2016)
To measure the density of the superficial retinal small vessel network (SRSVN), superficial retinal capillary network (SRCN), deep retinal capillary network (DRCN), and choriocapillaris and the size of the foveal avascular zone (FAZ) in the superficial retinal layer in normal eyes. Prospective observational cross-sectional study. In healthy Chinese volunteers, the retinal and choroidal vasculature was visualized by split-spectrum amplitude decorrelation angiography–associated optical coherence tomography (RTVueXR Avanti device; Optovue Inc, Fremont, California, USA). Among 105 healthy participants (age: 35.9 ± 13.8 years) mean FAZ measured 0.35 ± 0.12 mm2, and mean density of SRSVN, SRCN, DRCN, and choriocapillaris was 8.54% ± 0.92%, 31.8% ± 2.6%, 45.8% ± 3.3%, 44.4% ± 3.3%, and 44.5% ± 2.7%, respectively. In multivariate analysis, higher SRSVN density was associated with younger age (P = .001; standardized regression coefficient β: −0.28), male sex (P = .008; β: −0.23), lower SRCN density (P < .001; β: −0.40), and larger mean choriocapillaris vessel diameter (P = .001; β: 0.30). Higher SRCN density was correlated with male sex (P = .007; β: −0.19), lower SRSVN density (P < .001; β: −0.44), and higher density of the radial peripapillary capillary density (P = .004; β: 0.20). Higher DRCN density was correlated with younger age (P < .001; β: −0.31), female sex (P = .002; β: 0.22), higher SRCN density (P < .001; β: 0.38), and higher choriocapillaris density (P < .001; β: 0.39). Higher choriocapillaris network density in the central region was associated with higher DRCN density (P < .001; β: 0.43) and lower radial peripapillary capillary density (P = .005; β: −0.26). All retinal vascular parameters were not significantly correlated with axial length or subfoveal choroidal thickness. The density of the macular vascular networks decreases with older age and is independent of axial length and subfoveal choroidal thickness in healthy individuals.